TINJAUAN YURIDIS TENTANG PERLINDUNGAN KONSUMEN PERDAGANGAN MELALUI ELEKTRONIK DI INDONESIA - Theodosiva Yovita (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2003)
“Importance trading consumer protection by means of electronic, that represents a global issue in the world nowadays. Producers in promoting their product by means of cyber world (internet) frequently mislead and promise things that unavailable in their products. In order to provide consumer protection against misleading products or services, it is necessary to have evidences submitted by consumers. The required evidences are evidently cannot be fulfilled by consumers due to limits of formal proving means in heaving disputes both in courts and other institutions that settle disputes of consumers with producers. Indonesian laws still apply formal proof to win cases